Pembelaan Diri Kepolisian Terhadap Pelaku Kejahatan yang Melakukan Perlawanan - Saputra, Iswandy Rani (Jurnal Litigasi Amsir, 2022)
This research was conducted to find out how police discretion forms against criminals who resist and to find out how the Indonesian National Police carry out the factors that influence police discretion. The type of research used in this research is normative and empirical research. Normative research is an approach that is carried out by analyzing applicable laws, theories, and written concepts related to the problems to be studied. In contrast, empirical research is research carried out with field data as the primary data source, such as the results of interviews and observations. The results of this study indicate that the Use of Police Discretion must refer to laws and regulations both in the Police Act and the Protap Kapolri Number 1 of 2010 concerning the prevention of anarchism, where the police can take decisive action in the form of shots that can paralyze the perpetrators if the actions of the perpetrators can harm members police and society. The use of discretion is not an authority. Still, police actions must be accounted for based on applicable laws and norms and the factors that cause police discretion to be exercised. Namely, the perpetrators do not heed the appeals of members in the field, such as warning shots and calls to surrender, or the perpetrators put up resistance against members of the community or the community. who was at the scene.